2000
DOI: 10.1074/jbc.275.14.10030
|View full text |Cite
|
Sign up to set email alerts
|

The Two Halves of CFTR Form a Dual-pore Ion Channel

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) exhibits two conductance states, 9 picosiemens (pS) and 3 pS. To investigate the origin of these two distinct conductance states, we measured the single-channel activity of three truncated forms of CFTR. These include: TNR, which contains the first transmembrane domain, the first nucleotide binding domain, and the R domain; RT2N2, which contains the R domain, the second transmembrane domain, and the second nucleotide-binding domain; and T2N2, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 24 publications
0
31
2
Order By: Relevance
“…In this trace the downward deflections likely represent Cl Ϫ movement across the cellular membrane. The gating of this channel, with quick bursts of activity interrupted by brief flickering closures, is not different from the normal channel characteristics of CFTR that have been described by others (23,30). The conductance of this anion channel is shown in Fig.…”
Section: Immunolocalization Of Alveolar Cells For Patch Clamp Analysimentioning
confidence: 83%
“…In this trace the downward deflections likely represent Cl Ϫ movement across the cellular membrane. The gating of this channel, with quick bursts of activity interrupted by brief flickering closures, is not different from the normal channel characteristics of CFTR that have been described by others (23,30). The conductance of this anion channel is shown in Fig.…”
Section: Immunolocalization Of Alveolar Cells For Patch Clamp Analysimentioning
confidence: 83%
“…These data demonstrate that treatment of defective airway cells with myoinositol or betaine for 24 h caused a significant amount of ⌬F508 CFTR to reach the cell surface membrane and restore the chloride channel function of both ⌬F508 CFTR and ORCC channels. However, the treatment with organic solutes did not restore the open probability of ⌬F508 CFTR to the level of WT CFTR, which has a P o value of about 0.6 (29).…”
Section: Effect Of Myoinositol On the Thermal Stability Of Nbd1 And ⌬mentioning
confidence: 99%
“…The paths of both shafts join at the bottom into a common chamber. Interestingly, it has been reported that CFTR may be a double-barreled ion channel (36). The CFTR molecule elongates downwards into a more open lower density region (Fig.…”
Section: Cftr Expression Purification and Hydrolysis Of Atp-thementioning
confidence: 99%